Leaving footprints on online brand communities: the role of positive and negative engagement on commitment - Bilro, R.G.; Loureiro, S. M. C.; Guerreiro, J. (The European Marketing Academy Conference - EMAC 2017, 2017)
The aim of the current study is to explore the influence of online brand communities on committing participants to love/hate online brand communities. Three brands are selected to be the focus of the study (Starbucks, Apple, and McDonald’s) and six online brand communities of such brands participate (three fan brand communities or love communities and three anti-brand communities or hate communities). The online questionnaire is fulfilled by 600 members of such communities. Findings reveal the importance of Brand passion, Rewards(hedonic) and Validation to be committed to love brand communities and other three dimensions to be committed to hate brand communities: Brand influence, Helping, and Self-expression.